2018
DOI: 10.1002/ecy.2064
|View full text |Cite
|
Sign up to set email alerts
|

Latitude, temperature, and habitat complexity predict predation pressure in eelgrass beds across the Northern Hemisphere

Abstract: Abstract. Latitudinal gradients in species interactions are widely cited as potential causes or consequences of global patterns of biodiversity. However, mechanistic studies documenting changes in interactions across broad geographic ranges are limited. We surveyed predation intensity on common prey (live amphipods and gastropods) in communities of eelgrass (Zostera marina) at 48 sites across its Northern Hemisphere range, encompassing over 37°of latitude and four continental coastlines. Predation on amphipods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 35 publications
1
50
1
Order By: Relevance
“…Removing SAV comparisons from the dataset yielded a nonsignificant effect of latitude ( p = .063), indicating that this trend in our analysis was also driven primarily by SAV. An alternative but not mutually exclusive explanation might be the paradigm of decreasing predation with increasing latitude (Schemske, Mittelbach, Cornell, Sobel, & Roy, ), which leads to higher juvenile survival and increased densities in temperate regions, as has been shown recently in a global comparative seagrass experiment (Reynolds et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…Removing SAV comparisons from the dataset yielded a nonsignificant effect of latitude ( p = .063), indicating that this trend in our analysis was also driven primarily by SAV. An alternative but not mutually exclusive explanation might be the paradigm of decreasing predation with increasing latitude (Schemske, Mittelbach, Cornell, Sobel, & Roy, ), which leads to higher juvenile survival and increased densities in temperate regions, as has been shown recently in a global comparative seagrass experiment (Reynolds et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…We present predator consumption rates of the predator guild as a whole due to the difficulty of assessing per capita rates with fixed‐area video (as unmarked individuals leave and re‐enter the field of view), but per capita rates may also be higher in the tropics given the expectation of increased metabolic activity in warmer ocean waters (Iles, ). Nearshore predation rates, however, can be more strongly predicted by annual mean temperatures than in situ temperatures at the time of predation assays, suggesting the interaction between predation and temperature may be more complex than simply increased metabolic demands (Reynolds et al, ). Field observations and data presented here suggest, however, that predator activity can be quite spatially and temporally variable in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger biotic interactions at lower latitudes have been proposed as a central mechanism to help explain both the evolutionary origin and ecological maintenance of the latitudinal diversity gradient and high tropical biodiversity (Dobzhansky, 1950;Mittelbach et al, 2007;Schemske, 2002;Schemske, Mittelbach, Cornell, Sobel, & Roy, 2009). For predation in particular, the strength and generality of a change in interaction strength with latitude are receiving increased empirical interest (Lavender, Dafforn, Bishop, & Johnston, 2017;Reynolds et al, 2018;Roslin et al, 2017;Sheppard-Brennand, Dworjanyn, & Poore, 2017), but standardized biogeographic comparisons remain few. We are also at the early stages of understanding community consequences of a change in interaction strength across latitude and the role of predation in shaping contemporary patterns of diversity (Freestone & Inouye, 2015;Freestone, Osman, Ruiz, & Torchin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…complementarity; Duffy et al, ; Micheli & Halpern, ). It has, however, also been suggested that low redundancy and high complementarity can characterize animal assemblages and ecological functions on coral reefs (Brandl & Bellwood, ; D'agata et al, ), in kelp forests (Ling, Johnson, Frusher, & Ridgway, ; Micheli & Halpern, ) and over seagrass meadows (Duffy et al, ; Reynolds et al, ), where herbivory and piscivory are frequently performed by a small suite of species (Bellwood et al, ; Duffy et al, ; Martin et al, ). New research suggests that low redundancy and high complementarity might also be features of animal assemblages in estuaries, coastal bays and on ocean beaches (Bingham et al, ; Gilby, Tibbetts, & Stevens, ; Olds, Frohloff, et al, ).…”
Section: Introductionmentioning
confidence: 99%